2011
DOI: 10.1155/2011/273241
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Bladder Cancer with Cavitary Lung Metastases

Abstract: Transitional cell carcinoma (TCC) of the bladder tends to remain superficial; however, in 5% to 20% of cases, it progresses to muscle invasion and, more rarely, can metastasize. TCC of the bladder primarily spreads via regional lymphatics. The most common sites of distant metastases of TCC are the liver, lung, mediastinum and bone. Longterm survival of patients with metastatic bladder cancer is rare. Patterns of pulmonary metastasis include multiple nodules, a solitary mass or interstitial micronodule. When mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Cavitary pulmonary metastasis often accompanies squamous cell carcinoma of the head, neck, and cervix, as well as gastrointestinal tract adenocarcinoma, gallbladder cancer, bladder cancer, and ovarian adenocarcinoma and osteosarcoma. [10][11][12][13][14][15] The chest CT findings in this patient were multiple annular cavities and a cystic cavity in bilateral lungs. TBLB confirmed metastatic lung adenocarcinoma, which was homogeneous with cholangiocarcinoma, thus suggesting that the lung metastasis of cholangiocarcinoma was pleomorphic.…”
Section: Discussionmentioning
confidence: 99%
“…Cavitary pulmonary metastasis often accompanies squamous cell carcinoma of the head, neck, and cervix, as well as gastrointestinal tract adenocarcinoma, gallbladder cancer, bladder cancer, and ovarian adenocarcinoma and osteosarcoma. [10][11][12][13][14][15] The chest CT findings in this patient were multiple annular cavities and a cystic cavity in bilateral lungs. TBLB confirmed metastatic lung adenocarcinoma, which was homogeneous with cholangiocarcinoma, thus suggesting that the lung metastasis of cholangiocarcinoma was pleomorphic.…”
Section: Discussionmentioning
confidence: 99%
“…Kurian et al (10) reported a case of urothelial bladder cancer with cavitary lung metastases, which exhibited a large irregular cavity surrounded by a wall of uneven thickness. This type of cavity is formed by central ischemic necrosis with the progression of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Age/Sex Presenting pulmonary symptoms Pulmonary manifestation Alexander et al, 1990 [3] 52/male Persistent cough Post primary TCC resection Multiple nodules, several with cavitation 56/male Non-productive cough Post primary TCC resection Multiple nodules, several with cavitation Angulo et al, 1993 [6] 65/male Non-productive cough, fever, weight loss Solitary capsulated cavernous lesion on CT 76/male Asymptomatic Post primary TCC resection pulmonary nodules, some with cavitation Fiorelli et al, 2011 [7] 69/male Productive sputum and hemoptysis Post primary TCC resection LUL cavitating mass Kurian et al, 2011 [8] 59/male Hemoptysis Post primary TCC resection bilateral cavitated lesions advances have been made in the treatment of TCC there are unavoidable adverse effects of these agents.…”
Section: Author Yearmentioning
confidence: 99%